Economic evaluation of GPs' direct access to computed tomography for identification of brain tumours. (13th November 2020) - Keeney, Edna; Mohiuddin, Syed; Zienius, Karolis; Ben‐Shlomo, Yoav; Ozawa, Mio; Grant, Robin; Hamilton, William; Weller, David; Brennan, Paul M.; Hollingworth, William
Abstract: Background: When GPs suspect a brain tumour, a referral for specialist assessment and subsequent brain imaging is generally the first option. NICE has recommended that GPs have rapid direct access to brain imaging for adults with progressive sub‐acute loss of central nervous function; however, no studies have evaluated the cost‐effectiveness. Methods: We developed a cost‐effectiveness model based on data from one region of the UK with direct access computed tomography (DACT), routine data from GP records and the literature, to explore whether unrestricted DACT for patients with suspected brain tumour might be more cost‐effective than criteria‐based DACT or no DACT. Results: Although criteria‐based DACT allows some patients without brain tumour to avoid imaging, our model suggests this may increase costs of diagnosis due to non‐specific risk criteria and high costs of diagnosing or 'ruling out' brain tumours by other pathways. For patients diagnosed with tumours, differences in outcomes between the three diagnostic strategies are small. Conclusions: Unrestricted DACT may reduce diagnostic costs; however, the evidence is not strong and further controlled studies are required. Criteria‐based access to CT for GPs might reduce demand for DACT, but imperfect sensitivity and specificity of current risk stratification mean that it will not necessarily be cost‐effective.